Patterns of ventricular contraction in patients with conduction abnormality studied by radionuclide angiocardiography. Issue 5 (May 1984) - Underwood, S R; Walton, S; Laming, P J; Ell, P J; Emanuel, R W; Swanton, R H
Abstract : The phase image generated by radionuclide angiocardiography illustrates the regional timing of ventricular wall motion. In this study the phase image was used to investigate the patterns of ventricular contraction in 103 subjects with either normal hearts or a conduction abnormality. In 38 normal subjects the right ventricle contracted on average 7 ms after the left, and the last region to contract was the right ventricular outflow tract. In 15 subjects with left bundle branch block the left ventricle contracted 69 ms after the right, contraction spreading from the septum to the lateral wall. In 12 subjects with right bundle branch block right ventricular contraction occurred 54 ms after the left. In 11 subjects with right bundle branch block and left anterior fascicular block both right and left ventricular contraction were delayed, the right more so than the left. In three of five subjects with the Wolff-Parkinson-White syndrome and four with frequent ventricular extrasystoles areas of early contraction corresponded to areas of early depolarisation. It is concluded that ventricular contraction can be studied non-invasively and follows a pattern to be expected from the pattern of electrical depolarisation.